Polymer emulsion composite modified road base material and preparation method thereof

By chemically hybridizing VAE copolymer emulsion with supersulfate cement and silane coupling agent, the problems of high cost and low early strength of polymer-modified road base materials have been solved, resulting in road base materials with high durability and crack resistance, reducing material costs and improving early strength and durability.

CN121318339APending Publication Date: 2026-01-13RES INST OF HIGHWAY MINIST OF TRANSPORT
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511635477.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-10
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

Existing polymer-modified road base materials present a contradiction between high cost and low early strength, and the interfacial bond between traditional polymers and cement is weak, resulting in poor durability.

Method used

A chemical hybrid system is adopted, which combines domestically produced vinyl acetate-ethylene (VAE) copolymer emulsion with supersulfate cement or geopolymer cement, and silane coupling agent. Through rapid hydration, an early strength skeleton is constructed, chemical chelation thickening and chemical cross-linking network are formed, thus forming an organic-inorganic hybrid network.

Benefits of technology

It has achieved a low-cost, high early strength, good durability, and near-zero shrinkage road base material, which meets construction requirements and improves the material's crack resistance, hydrolysis resistance, and freeze-thaw resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121318339A_ABST
    Figure CN121318339A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer emulsion composite modified road base material and a preparation method thereof, and belongs to the technical field of traffic infrastructure engineering materials. The polymer emulsion composite modified road base material is prepared from the following raw materials: graded aggregate, super sulfate cement or geopolymer cement, water for mixing, vinyl acetate-ethylene (VAE) copolymer emulsion and a silane coupling agent. The preparation method comprises the following steps: mixing the VAE emulsion with water for mixing to obtain a polymer diluent; mixing graded aggregate with an inorganic cementing material, then adding the polymer diluent, and mixing to obtain a mixture; and then paving, compacting, forming and curing are carried out. By forming a VAE flexible network-C-S-H / ettringite hybrid network, the material has the remarkable advantages of higher mechanical strength and low cost, and can greatly improve and enhance the crack resistance and durability of the road base.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of infrastructure engineering materials technology, and particularly relates to a polymer emulsion composite modified road base material and its preparation method. Background Technology

[0002] In the field of modern road engineering, semi-rigid base courses (especially cement-stabilized crushed stone) have become the most widely used pavement base course materials due to their significant advantages of high load-bearing capacity, high slab stiffness, and economical cost. However, this type of base course also has inherent defects, specifically shrinkage cracking, transverse cracks leading to reflective cracking, and water damage to the pavement, which have become typical defects affecting the service performance of semi-rigid base asphalt pavements.

[0003] To overcome these challenges, introducing water-based polymers (such as emulsions) into base materials to prepare and utilize flexible base layers with high mechanical properties is a solution. However, current technology faces the following bottlenecks: Bottleneck 1: The contradiction between high cost and low early strength Existing polymer modification technologies, such as those using imported acrylate-based SAEs or styrene-acrylates, are costly. On the other hand, if pure polymer stabilization is used, the early strength (such as 3-day unconfined compressive strength) is extremely low, making it difficult to meet the engineering requirements of construction compaction and early traffic opening (24-hour light load opening).

[0004] Bottleneck 2: Limitations of physical modification mechanisms Traditional polymer-cement composites (such as ordinary silicate cement) rely heavily on the physical encapsulation and spatial entanglement of the polymer film. The lack of strong chemical bonds between the polymer and inorganic hydration products (such as CSH gel) results in weak organic-inorganic interfacial adhesion. This superficial physical synergy makes the interface susceptible to damage under water exposure and freeze-thaw cycles (such as the "water-resistant and freeze-resistant" challenge), leading to durability failure.

[0005] Therefore, there is an urgent need in this field for a new material system and supporting process that can simultaneously overcome the bottlenecks of "high cost" and "low early strength" in polymer modification, and break through the defects of traditional technologies to achieve chemical synergistic effect between polymer flexible network and inorganic rigid skeleton. Summary of the Invention

[0006] To address the technical challenges of high cost, insufficient early strength, weak interfacial bonding, and poor durability of polymer base layers in the prior art, this invention proposes a polymer emulsion composite modified road base layer material and its preparation method.

[0007] This invention provides a three-in-one solution integrating material system innovation, synergistic mechanism innovation, and preparation process innovation. Breaking through the limitations of traditional material systems, this invention innovatively constructs a chemical hybrid system of "domestic vinyl acetate-ethylene (VAE) copolymer emulsion + supersulfate cement / geopolymer cement + silane coupling agent".

[0008] The superior performance of the material prepared by this invention stems from its unique organic-inorganic chemical hybrid synergistic curing mechanism, which is specifically achieved through the following three synergistic stages: I. Rapid Construction of Inorganic Rigid Skeleton: Achieving Early Strength This invention abandons ordinary silicate cement, which has a slow hydration rate, and instead uses supersulfate cement or geopolymer cement. This type of cement has a fast hydration rate and can quickly generate hydration products such as CSH gel and ettringite (AFt) in a very short time (e.g., 3 days), rapidly constructing the early strength skeleton of the material (3-day strength reaches 2.0-2.5 MPa), completely solving the shortcoming of low early strength of traditional polymer base layers.

[0009] II. Organic-inorganic chemical chelation: interfacial adhesion enhancement The VAE emulsion used in this invention incorporates a specific functional monomer—acetyl methacrylate (AAEM)—during the polymerization stage. During the subsequent dehydration curing process, the AAEM groups can react with the Ca released during the hydration of inorganic cement. 2+ A strong chelation reaction occurs. This chemical chelation acts like a "molecular rivet," establishing an interfacial bond between the organic and inorganic phases that far exceeds that of physical adsorption (the peel strength is increased by 2 times), forming a "flexible-rigid" bicontinuous phase.

[0010] III. Chemical cross-linking network: enhancing durability This invention introduces a silane coupling agent (such as KH-560) into the system. During the dehydration and curing stage, the silane coupling agent undergoes hydrolysis and condensation, with one end reacting with the functional groups of the VAE emulsion and the other end chemically reacting with the -OH groups on the surface of the inorganic hydration product (CSH / ettringite) to form a dense Si-OM (metal) covalent bond. This chemical crosslinking network (Hybrid Network) greatly improves the compactness, water resistance (water absorption rate reduced from 5.5% to 2.8%), and freeze-thaw resistance of the composite material (mass loss <1% after 25 freeze-thaw cycles).

[0011] To achieve the above objectives, the present invention provides the following technical solution: One of the objectives of this invention is to provide a polymer emulsion composite modified road base material, comprising the following raw materials in parts by weight: 1000 parts of graded aggregate, 5-20 parts of supersulfate cement or geopolymer cement, 30-55 parts of mixing water, 3-10 parts of vinyl acetate-ethylene (VAE) copolymer emulsion, and 0.05-0.30 parts of silane coupling agent.

[0012] Furthermore, the graded aggregate is continuously graded limestone crushed stone with a maximum particle size of 31.5 mm and a fine material content of 0-5 mm of 30-40 wt%.

[0013] Furthermore, the VAE emulsion has a solids content of 48-55 wt%, with ethylene monomer accounting for 15-25 wt% of the emulsion solids, a glass transition temperature (Tg) of -12℃ to -8℃, a pH of 8.0-9.5, a 180° peel strength of 0.6-1.8 N / mm, and a calcium ion complexation index greater than 1.2; the silane coupling agent is γ-glycidoxypropyltrimethoxysilane (KH-560) and / or isobutyltriethoxysilane (IBTES).

[0014] Furthermore, the supersulfate cement is a mixture of granulated slag ≥70wt%, anhydrous gypsum 10-15wt%, and silicate clinker 5-10wt%; the geopolymer cement is formed by fly ash / slag activated by Na2SiO3 / NaOH, and the CaO / SiO2 molar ratio is 0.8-1.2.

[0015] Furthermore, the VAE copolymer emulsion is preferably prepared by "one-step semi-continuous seed emulsion polymerization", which uses medium-temperature polymerization at 55-65℃, without the need for a low-temperature oxidation-reduction system, making the process user-friendly and easy to scale up.

[0016] The second objective of this invention is to provide a method for preparing a polymer emulsion composite modified road base material, comprising the following steps: Step 1, premixing: Shear the VAE emulsion with all the mixing water at 400-600 rpm for 1-2 minutes to obtain a polymer dilution; The second step is to coat the aggregate with slurry: dry mix the graded aggregate with supersulfate cement or geopolymer cement for 15-20 seconds, add the diluted solution within 60 seconds, and continue to wet mix for 120-150 seconds to obtain the mixture. The third step, material curing, molding, and dehydration treatment: The mixture is subjected to static curing, followed by spreading and compaction. The compacted base layer is then subjected to dehydration treatment until its residual moisture content reaches a preset standard. This process drives VAE demulsification and film formation, and completes the aforementioned chelation and cross-linking reactions with inorganic hydration products to form a hybrid network.

[0017] Furthermore, the time for the static curing process is ≥1 hour.

[0018] Furthermore, the compaction degree after compaction is ≥98%.

[0019] Furthermore, the moisture content is ≤1.6%.

[0020] The third objective of this invention is to provide an application of polymer emulsion composite modified road base material in the construction of base courses for highways, airport runways, or heavy-duty traffic pavements.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects: (a) Significant low-cost advantage This invention uses domestically produced VAE emulsion, which reduces costs. At the same time, the solid content of VAE emulsion (>50%) is higher than that of traditional emulsions, which can reduce transportation costs and construction mixing water, resulting in significant overall economic benefits.

[0022] (b) Excellent early strength performance This invention uses fast-setting supersulfate / geopolymer cement, combined with AAEM and Ca in VAE. 2+ The chemical chelation mechanism enables "early strength hybridization". The 3-day unconfined compressive strength can reach 2.0-2.5MPa, meeting the stringent requirement of light load opening 24 hours after construction, and solving the industry pain point of low early strength of traditional polymer base layers.

[0023] (c) Excellent durability This invention introduces Si-OM covalent bonds through a silane coupling agent, achieving chemical cross-linking at the organic-inorganic interface. This hybrid network significantly reduces the material's water absorption rate (e.g., from 5.5% to 2.8%), with a mass loss of less than 1% after 25 freeze-thaw cycles, exhibiting excellent hydrolysis resistance and freeze-thaw resistance.

[0024] (d) Polymer emulsion preparation process is user-friendly The VAE emulsion is produced by one-step polymerization at a medium temperature of 55-65℃, without the need for a harsh oxidation-reduction low-temperature system. The process is stable and easy to scale up in large reactors (e.g., 10t), and the emulsion has a uniform particle size distribution (PDI < 0.1). Attached Figure Description

[0025] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 The diagram shows the drying shrinkage strain and drying shrinkage coefficient of the material prepared in Example 1 over 60 days. Figure 2 The diagram shows the thermal shrinkage strain and thermal shrinkage coefficient of the material prepared in Example 1 in different temperature ranges. Detailed Implementation

[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0027] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0030] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0031] This invention provides a method for preparing a polymer emulsion composite modified road base material, comprising the following steps: 1) Premixing: Mix the vinyl acetate-ethylene (VAE) copolymer emulsion, silane coupling agent and all the mixing water, and shear at 400-600 rpm for 1-2 min to obtain a polymer dilution. 2) Coating: The graded aggregate and inorganic cementitious material (supersulfate cement or geopolymer cement) are put into the mixing equipment and dry-mixed for 15-20 seconds. Then, the polymer dilution obtained in step 1) is added within 60 seconds, and wet mixing is continued for 120-150 seconds to obtain the mixture. 3) Curing and Molding: The well-mixed material is allowed to stand for curing before being spread and compacted into shape; 4) Dehydration curing: The compacted base layer is naturally ventilated to dehydrate and promote VAE demulsification and film formation, and form a hybrid network with inorganic hydration products (CSH / ettringite) until its residual moisture content reaches the predetermined value, thus obtaining polymer emulsion composite modified road base material.

[0032] In the following optional embodiments of the present invention, the time for the static curing process is ≥1 hour.

[0033] In the following optional embodiments of the present invention, the compaction degree after compaction molding is ≥98%.

[0034] In the following optional embodiments of the present invention, the moisture content is ≤1.6%.

[0035] The above preparation method can be used to prepare a polymer emulsion composite modified road base material, which includes the following raw materials in parts by weight: 1000 parts of graded aggregate, 5-20 parts of supersulfate cement or geopolymer cement (exemplary, such as 15 parts), 3-10 parts of vinyl acetate-ethylene (VAE) copolymer emulsion (exemplary, such as 3 parts, 6 parts or 10 parts), 0.05-0.30 parts of silane coupling agent (exemplary, such as 0.15 parts), and 30-55 parts of mixing water (exemplary, such as 40 parts).

[0036] In the following preferred embodiments of the present invention, the graded aggregate is continuously graded limestone crushed stone with a maximum particle size of 31.5 mm and a fine material content of 0-5 mm of 30-40 wt%.

[0037] In the following optional embodiments of the present invention, the VAE copolymer emulsion is prepared according to claim 3, with a solid content of 48-55 wt%, ethylene monomer accounting for 15-25 wt% of the emulsion solids, and a glass transition temperature Tg of -12°C to -8°C.

[0038] In the following optional embodiments of the present invention, the inorganic cementitious material is supersulfate cement (SSC), which is composed of granulated slag ≥70wt%, anhydrous gypsum 10-15wt%, and silicate clinker 5-10wt%.

[0039] In the following optional embodiments of the present invention, the silane coupling agent is γ-glycidoxypropyltrimethoxysilane (KH-560). The polymer emulsion composite modified road base material can be used in the construction of base courses for highways, airport runways, or heavy-duty traffic pavements.

[0040] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.

[0041] Unless otherwise specified, the term "parts" in this invention refers to parts by weight.

[0042] All raw materials used in this invention are either purchased from the market or prepared using conventional methods in the field.

[0043] To further illustrate the technical solution of the present invention, the following embodiments are provided for further explanation.

[0044] The graded aggregates used in the examples and comparative examples are all continuously graded limestone crushed stone with a maximum particle size of 31.5 mm. Specifically, the mass ratio of 20-31.5 mm, 10-20 mm, 5-10 mm, and 0-5 mm is 32:18:15:35 (that is, the content of 0-5 mm fine material is 35%, which is within the range of 30-40 wt% in claim 4). If the particle size of a particle is exactly equal to the boundary value of two ranges, then it belongs to the range with that value as the lower limit.

[0045] The VAE emulsion used in the examples was a domestically produced VAE emulsion prepared according to claim 3 (52% solids, 20% ethylene, containing AAEM).

[0046] The inorganic cementing material used in the examples is supersulfate cement (SSC).

[0047] The silane coupling agent used in the examples is KH-560.

[0048] The polymer used in the comparative example was imported SRX emulsion (styrene-acrylate emulsion, solid content 45%).

[0049] The conventional cement used in the comparative example was PO 42.5 grade ordinary Portland cement.

[0050] Example 1 A polymer emulsion composite modified road base material, comprising the following raw materials in parts by weight: 1000 parts graded crushed stone, 15 parts supersulfate cement, 6 parts VAE emulsion, 0.15 parts KH-560, and 40 parts mixing water.

[0051] The preparation method is as described in the general steps above: 1) Premixing: Mix 6 parts VAE emulsion, 0.15 parts KH-560 and 40 parts water, stir for 1 minute to obtain a polymer dilution; 2) Coating: Add 1000 parts of graded crushed stone and 15 parts of supersulfate cement to the mixing equipment and dry mix for 20 seconds. Add the diluent from step 1) and wet mix for 120 seconds to obtain the mixture. 3) Curing and Molding: The mixture is allowed to stand for 1 hour, then spread and compacted to a compaction degree of 98%; 4) Dehydration curing: Place in a ventilated area for dehydration curing until the residual moisture content is below 1.6%.

[0052] Example 2 A polymer emulsion composite modified road base material, comprising the following raw materials in parts by weight: 1000 parts graded crushed stone, 15 parts supersulfate cement, 3 parts VAE emulsion, 0.15 parts KH-560, and 40 parts mixing water.

[0053] The preparation method is the same as in Example 1.

[0054] Example 3 A polymer emulsion composite modified road base material, comprising the following raw materials in parts by weight: 1000 parts graded crushed stone, 15 parts supersulfate cement, 10 parts VAE emulsion, 0.15 parts KH-560, and 40 parts mixing water.

[0055] The preparation method is the same as in Example 1.

[0056] Comparative Example 1 A comparative base material is provided to simulate conventional cement-stabilized crushed stone (i.e., traditional semi-rigid base) and to compare the technological advancements of this invention in terms of shrinkage cracking performance.

[0057] The raw materials include: 1000 parts graded crushed stone, 50 parts PO 42.5 grade ordinary Portland cement (note: equivalent to the industry-standard 5% cement admixture), and 45 parts mixing water. This mix does not contain any polymer emulsions or silane coupling agents.

[0058] Its preparation method adopts the conventional semi-rigid base course construction process in this field: 1) Mixing of the mixture: Add graded crushed stone, PO 4.25 cement and water into the mixing equipment and wet mix for 3 minutes; 2) Molding: Spread the well-mixed material and compact it to 98% compaction degree; 3) Moisturizing Curing: Place the molded specimens in a standard curing room (temperature 20±2℃, relative humidity ≥95%RH) for moisturizing curing for 7 days. Note: This curing method is fundamentally different from the "dehydration curing" process required by this invention.

[0059] Comparative Example 2 A comparative base material has a formulation that is basically the same as that of Example 1 of the present invention, but the key technical feature of silane coupling agent (KH-560) is intentionally omitted. The purpose of this is to verify the necessity of the silane coupling agent for achieving the high durability (especially water resistance and freeze-thaw resistance) of the present invention.

[0060] Its raw materials include: 1000 parts graded crushed stone, 15 parts supersulfate cement, 6 parts VAE emulsion, and 40 parts mixing water, but the amount of KH-560 is 0 parts.

[0061] Its preparation method is the same as that in Example 1 of the present invention (the only difference is in step 1, premixing: 6 parts of VAE emulsion are mixed and stirred with 40 parts of water, and the diluted solution does not contain KH-560).

[0062] Performance testing: To verify the beneficial effects of the present invention, the material specimens prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests according to the relevant provisions of the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" (JTG E51-2009) and the "Test Procedure for Cement and Cement Concrete in Highway Engineering" (JTG 3430-2020): 3-day unconfined compressive strength (UCS), 28-day unconfined compressive strength (UCS), 60-day drying shrinkage coefficient, and freeze-thaw splitting strength ratio (TSRR). The test results are summarized in Table 1.

[0063] Table 1. Comparison of performance indicators of materials prepared in Examples 1-3 and Comparative Examples 1-2 As shown in Table 1, the technical solution of this invention has significant technological advancements in key performance aspects compared to the comparative material. A detailed analysis follows: 1) The 60-day drying shrinkage coefficient of Comparative Example 1 (traditional 5% cement semi-rigid base course) is as high as 48.8 × 10⁻⁶. -5 This value is the root cause of the persistent shrinkage cracking problem in traditional semi-rigid substrates, a technical pain point that the industry urgently needs to address. The 60-day drying shrinkage coefficient of Example 1 of this invention is only 3.9 × 10⁻⁶. -5 Compared to Comparative Example 1, the shrinkage rate is as high as 92%, achieving "near-zero shrinkage". This key technological advancement stems from the fact that this invention uses a VAE flexible network to fill, constrain, and toughen the hydration product skeleton of inorganic cement, solving the brittleness and shrinkage problems of traditional cement-based materials from a material constitutive perspective. This results in excellent crack resistance and meets the requirement of claim 1 for a 60-day drying shrinkage coefficient ≤4×10⁻⁶. -5 Technical requirements.

[0064] 2) One of the core innovations of this invention lies in the construction of a stable organic-inorganic chemical bonding network. Comparative Example 2 (silane-free system) was set up to verify the necessity of this chemical hybridization (especially silane crosslinking). Data shows that the freeze-thaw splitting strength ratio (TSRR) of Comparative Example 2 is only 76%, and its interfacial bonding strength deteriorates severely under freeze-thaw cycles, resulting in poor durability. In contrast, the TSRR of Example 1 (containing KH-560 silane coupling agent) jumps to 90%, meeting the requirement of TSRR ≥ 85% as described in claim 5.

[0065] This set of comparisons strongly demonstrates that the silane coupling agent used in this invention constructs a powerful chemical bridge between the VAE polymer and the inorganic hydration product (CSH / ettringite) through Si-OM covalent bonds during the dehydration curing stage. This chemical crosslinking is related to the AAEM groups and Ca in the VAE. 2+ The combined chemical chelation effect forms a stable "organic-inorganic hybrid network," which is the key to achieving high durability and high interfacial stability in this invention. Comparative Example 2, lacking silane crosslinking, exhibits a significant performance degradation, thus validating the innovation and necessity of the chemical hybridization mechanism in this invention.

[0066] 3) The 3d UCS of Embodiments 1, 2 and 3 of the present invention are all ≥2.1MPa, which meets the early strength target of 3d UCS ≥2.0MPa as described in claim 1, and can realize rapid construction and opening to traffic.

[0067] In summary, this invention replaces the high-cost polymers that rely on imports with specific material systems (such as domestically produced VAE emulsion and supersulfate cement), achieving a "qualitative leap" in both (1) crack resistance and (2) durability while significantly reducing the overall cost of materials. This invention successfully achieves a unified performance of high early strength, high durability, and near-zero shrinkage with excellent economic benefits.

[0068] Figure 1 The diagram shows the drying shrinkage strain and drying shrinkage coefficient of the material prepared in Example 1 over 60 days; from Figure 1 As can be seen, the drying shrinkage strain of the material in Example 1 mainly occurs within the first 15 days of its age, then rapidly decreases and tends to stabilize, with shrinkage essentially ceasing after 30 days; its drying shrinkage coefficient reaches its peak in the early stage of its age (about 7-8 days) and then gradually decreases and stabilizes, with the final drying shrinkage coefficient at 60 days stabilizing at approximately 3.9 × 10⁻⁶. -5 The low level indicates that the material has excellent drying shrinkage stability.

[0069] Figure 2 The graph shows the thermostatic strain and thermostatic shrinkage coefficient of the material prepared in Example 1 at different temperature ranges; from Figure 2 As can be seen, the thermal shrinkage strain of the material increases approximately linearly with decreasing temperature; however, the thermal shrinkage coefficient increases only slightly with decreasing temperature, remaining at only 4.7 × 10⁻⁶ even in the frigid temperature range of -10 to -20°C. -6 This indicates that the material has very low temperature sensitivity and good low-temperature crack resistance.

[0070] In summary, this invention utilizes a synergistic material system of specific VAE emulsion, supersulfate cement, and silane coupling agent, supplemented by specific preparation processes of "molding" and "dehydration curing," to construct an "organic-inorganic hybrid network" structure containing chemical chelation and covalent crosslinking within the base material.

[0071] As can be seen from the performance comparison of the above embodiments and comparative examples, the present invention successfully solves the shrinkage and cracking problem of traditional semi-rigid base layers (such as Comparative Example 1) with a significantly reduced overall cost, and solves the material durability problem through key chemical hybridization innovation (as demonstrated by Comparative Example 2), achieving a comprehensive technical effect of high early strength, high durability, and near-zero shrinkage. It has significant creative and practical value and excellent economic benefits.

[0072] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A polymer emulsion composite modified road base material, characterized in that, The raw materials comprise the following parts by weight: 1000 parts graded aggregate, 3-10 parts vinyl acetate-ethylene copolymer emulsion, 5-20 parts supersulfate cement or geopolymer cement, 30-55 parts mixing water, and 0.05-0.30 parts silane coupling agent; the vinyl acetate-ethylene copolymer emulsion has a solids content of 48-55 wt%, with ethylene monomer accounting for 15-25 wt% of the emulsion solids, a glass transition temperature Tg of -12℃ to -8℃, and a pH of [missing value]. Peel strength of 0.6-1.8 N / mm at 180° (8.0-9.5 mm); the silane coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane (KH-560) and / or isobutyltriethoxysilane; furthermore, after dehydration curing, the polymer emulsion composite modified road base material forms a VAE flexible network—CSH / ettringite hybrid network within the base layer, with a 3-day unconfined compressive strength ≥2.0 MPa and a 60-day drying shrinkage coefficient ≤4×10⁻⁶. -5 .

2. The polymer emulsion composite modified road base material according to claim 1, characterized in that, The graded aggregate is continuously graded limestone crushed stone with a maximum particle size of 31.5 mm and a fine material content of 0-5 mm of 30-40 wt%.

3. The polymer emulsion composite modified road base material according to claim 1, characterized in that, The vinyl acetate-ethylene copolymer emulsion is prepared by one-and-a-half-step continuous seed emulsion polymerization, including the following steps: (a) Pre-emulsify vinyl acetate, ethylene, emulsifier, and deionized water, and then free radical polymerize at 55-65°C to form seeds; (b) Simultaneously add the remaining monomer and 0.3-0.8 wt% acetyl methacrylate, and keep warm for 1.5-2 hours; (c) Cool to ≤45℃, add silane coupling agent and adjust pH to 8.5-9.0 to obtain high solids vinyl acetate-ethylene emulsion.

4. The polymer emulsion composite modified road base material according to claim 1, characterized in that, The supersulfate cement is a mixture of granulated slag ≥70wt%, anhydrous gypsum 10-15wt%, and silicate clinker 5-10wt%; and / or, the geopolymer cement is fly ash / slag activated by Na2SiO3 / NaOH, and the CaO / SiO2 molar ratio is 0.8-1.

2.

5. A method for preparing a polymer emulsion composite modified road base material as described in any one of claims 1-4, characterized in that, Includes the following steps: (a) Mix the vinyl acetate-ethylene emulsion with all the mixing water to obtain a polymer dilution; (b) The graded aggregate is mixed with the inorganic cementitious material, and then the polymer dilution is added. The mixture is wet-mixed to obtain the mixture. (c) The mixture is subjected to a static curing process, followed by spreading, compaction, and dehydration curing until the residual moisture content reaches a predetermined value; the dehydration curing promotes the demulsification and film formation of vinyl acetate-ethylene and the formation of a hybrid network with inorganic hydration products. This hybrid network is characterized by: the acetyl methacrylate ethyl ester groups on the surface of the vinyl acetate-ethylene particles reacting with the hydrated CaO of the inorganic cementitious material. 2+ A chelating bond is formed; the terminal -Si(OR)3 of the silane coupling agent condenses with the -OH on the surface of CSH / ettringite to form a Si-OM covalent bond; and the hybrid network makes the material have an unconfined compressive strength of ≥3MPa and a freeze-thaw splitting strength ratio of ≥85% after 28 days.

6. The preparation method according to claim 5, characterized in that, In step (a), shearing is performed at 400-600 rpm for 1-2 minutes; in step (b), the graded aggregate and inorganic cementitious material are first dry-mixed for 15-20 seconds, and then the diluent is added within 60 seconds, and wet mixing is continued for 120-150 seconds; the standing and curing treatment time is ≥1 hour, the ambient temperature is 15-35℃, and the relative humidity is 40-70%RH.

7. The preparation method according to claim 5 or 6, characterized in that, The compaction degree after compaction is ≥98%.

8. The preparation method according to any one of claims 5-7, characterized in that, The moisture content reaches the predetermined value of ≤1.6%.

9. The application of a polymer emulsion composite modified road base material as described in any one of claims 1-4 in the construction of base courses for highways, airport runways, or heavy-duty traffic pavements, characterized in that... If the base layer design deflection value is ≤30, no expansion joint is required.

Citation Information

Cited By

  • Preparation method of super-stain-resistant high-performance cement-based sealant

    CN121758127A

  • Preparation method of super-stain-resistant high-performance cement-based joint sealant

    CN121758127B